2008
DOI: 10.1177/0886260507312948
|View full text |Cite
|
Sign up to set email alerts
|

The Rosenzweig Picture-Frustration Study “Extra-Aggression” Score as an Indicator in Cognitive Restructuring Therapy for Male Perpetrators of Domestic Violence

Abstract: It was hypothesized that male perpetrators of domestic violence in the early stages of a 1-year process of cognitive restructuring therapy would manifest on the Rosenzweig Picture-Frustration Study higher levels of extra-aggressiveness than in later stages of the therapy process. A sample of male batterers in the process of treatment took the Rosenzweig instrument. The resulting responses were rated by trained scorers. Chi-square calculations revealed that batterers in the first quarter of treatment manifested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Another limitation to the study was the small sample size, and that all participants were voluntary. It is likely that response scores might be affected by a participant's mandatory assignment to the program, rather than his personal desire to participate, although the study by Norman and Ryan (2008) revealed similar results from a group of 90 court-ordered participants.…”
Section: Limitations Of the Projectsupporting
confidence: 60%
See 2 more Smart Citations
“…Another limitation to the study was the small sample size, and that all participants were voluntary. It is likely that response scores might be affected by a participant's mandatory assignment to the program, rather than his personal desire to participate, although the study by Norman and Ryan (2008) revealed similar results from a group of 90 court-ordered participants.…”
Section: Limitations Of the Projectsupporting
confidence: 60%
“…The participants were learning how to recognize their own prior acts of violence and how to use more effective means to express their thoughts, feelings, and needs, rather than earlier uses of control, intimidation and violence. Considering that only 22 of the 52 sessions could be completed during the allotted time, the results are encouraging and mirror those found by Norman and Ryan (2008). They assessed the change in batterers' aggression scores who were involved in a one-year cognitive-restructuring therapy.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The series of frustrating social situations are hypothetical; however, they refl ect regularly occurring social situations, such as being in the cinema or shopping. The RPFS has predominantly been used with forensic and medical populations, such as physically abused children (Kinard, 1980), men with a history of violence (Norman & Ryan, 2008) and patients with epilepsy (Sanyal & Banerjee, 2004). The RPFS may be particularly appropriate for measuring the regulation of anger or aggression in individuals with AN, as evidence suggests that anger is a highly salient emotion for this group (Fox & Harrison, 2008).…”
mentioning
confidence: 99%
“…Sigmund Freud was said to have used the concept "frustration" to explain the external and internal factors that inhibit needs satisfaction (Shorkey & Crocker, 1981). He noted that there were obstacles to attaining satisfaction which results in the change in behaviour that is being translated in aggression, regression, fixation and resignation (Norman & Ryan, 2008;Shorkey & Crocker, 1981;Young, 2009). Young maintains that "each of the four characteristics illustrates a continued state of experienced interpersonal conflict, and none of the feelings associated with the characteristics directly helps an individual to attain a goal or meet a need" (2009, p. 286).…”
Section: Theoretical Framework Underpinning the Context: The Frustratmentioning
confidence: 99%